1999
DOI: 10.1046/j.1365-3083.1999.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Systemic Lupus Erythematosus

Abstract: Lindqvist AKB, Alarcón-Riquelme ME. The Genetics of Systemic Lupus Erythematosus. Scand J Immunol 1999;50:562-571. There is considerable evidence that the development of systemic lupus erythematosus (SLE) has a strong genetic basis. For more than 20 years, much effort has been made to understand the genetics of SLE. Association studies in humans suggest the existence of genetic effects by the alleles encoded in the HLA, deficiencies in the complement genes and the low-affinity variants of Fc␥-receptors. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 79 publications
0
31
1
1
Order By: Relevance
“…Although some studies suggested an association with HLA-DR2 and HLA-DR3, the two best established MHC susceptibility loci for SLE, not all studies are in agreement regarding the role of the MHC in LN. 32,33 In our study that contrasts patients with LN with patients with lupus without nephritis, modest associations were observed with both of these MHC class II alleles (as assessed by proxies). Analyses conditioned on rs9271366 and rs2187668 indicate that loci outside of MHC class II genes may also contribute to LN risk, as seen in other studies of SLE.…”
Section: Discussioncontrasting
confidence: 54%
“…Although some studies suggested an association with HLA-DR2 and HLA-DR3, the two best established MHC susceptibility loci for SLE, not all studies are in agreement regarding the role of the MHC in LN. 32,33 In our study that contrasts patients with LN with patients with lupus without nephritis, modest associations were observed with both of these MHC class II alleles (as assessed by proxies). Analyses conditioned on rs9271366 and rs2187668 indicate that loci outside of MHC class II genes may also contribute to LN risk, as seen in other studies of SLE.…”
Section: Discussioncontrasting
confidence: 54%
“…More data about SLE genetics are beginning to emerge from candidate gene and linkage studies (9,36). We found evidence of multivariate linkage and linkage to malar rash, a hallmark feature of SLE, to chromosome 7p13.…”
Section: Discussionmentioning
confidence: 73%
“…Diverse genetic and environmental factors are implicated in its etiology. (1)(2)(3)(4) The association between SLE and polymorphisms at several loci, including the major histocompatibility complex (MHC), which encodes human leukocyte antigen (HLA), complement proteins, immunoglobulin receptors, cytokines, and other unmapped genes, has been stated by several genetic studies. (5,6) The genetic role of MHC is well studied, and association (7) as well linkage studies (8) undoubtedly demonstrated the presence of SLE susceptibility factors in the MHC region.…”
Section: Introductionmentioning
confidence: 99%